The Concept Of Ahl Al-Kitab: Recognition Adherents Of Ahl Al-Kitab - Nurul Hakim; Ali Fauzi (IAIN Ponorogo, 2021)
This paper will explore the existence of the ahl al-kitab . In exploring the existence of the ahl al-kitab , the writer traced it through the verses of the Qur’an. Furthermore, the understanding of these verses is sought according to the understanding of the experts. And then, the expert’s understanding is comprehensively analyzed. The ʻulama’ generally state that the so-called ahl al-kitab are the Jewish and Christian communities. However, among the ʻulama’, still give opportunity to have dialogue regarding the status of the ahl al-kitab. This is because the Qur’an explicitly mentions the existence of the ahl al-kitab, and discusses it. Based on the Qur’an, the definition of the ahl al-kitab has developed, namely the ahl al-kitab refers to the notion of religion which is aimed at communities or groups of religious adherents who have holy books that have been revealed by Allah SWT to the Prophet and His Messenger in general. In the narration taken from Ahmad bin Hanbal, it is stated that the number of Prophets is 124,000. Of the 124,000 prophets, 315 were sent to become Massengers, or in other narrations, 314 or 313 people were mentioned. Thus, the number of holy books that Allah sent to earth is the same number with the Massengers who were sent to that earth. Some of these Messengers were narrated by the Qur’an, and some of them were not narrated by Qur’an.